METHODS OF CONTROLLING DISTRIBUTION COSTS. - Hilgert, J. R. (The Accounting Review, 1927)
Abstract In recent times, many companies have cut selling cost materially because of better accounting control particularly of the field organization. Also, an increasing interest has been shown by sales executives in sales-cost accounting. The author attempts to show how sales-cost accounting can be made to aid sales executives. The discussion centers around defining and grouping, budgeting, and apportioning selling overhead costs. Various items which are charged to selling expense by some concerns are not so included by others. The wide variation in selling expense items no doubt to a large extent is due to the difference in the sales policies of organizations as well as a lack of a common conception of the functions of the sales department. Effective budgeting of expenses presupposes proper charting of the functions of an organization so that the responsibility of performing each function can be definitely fixed. It has been noted that cost of operating in each territory and the profit and loss of each give the sales manager a basis for reorganizing his sales districts so as to make the efforts of the sales people more effective.